The Relationship Between Illiteracy, Development, Poverty, and Equality - Alshebeili, Manal Saleh (Journal of Cultural Analysis and Social Change, 2026)
This study aims to clarify the relationship between illiteracy, development, poverty, and equality, considering illiteracy as one of the social and economic issues that directly affect the course of comprehensive development, income levels, and social equality. The study adopted the descriptive–analytical approach. The results confirmed that sustainable development in societies first requires combating illiteracy, as it constitutes the foundation of poverty, unemployment, and inequality of opportunities between genders. This can only be achieved through knowledge and learning, which require enrollment in education at all its stages and levels, with particular emphasis on intensifying literacy and adult education programs. This, in turn, necessitates the adoption of appropriate decisions and methods by governments and societies, as well as the participation of all governmental and civil sectors, to confront this problem and eliminate the sources of illiteracy